Analysis Of The Potential Of Entertainment Tax And Restaurant Tax In Increasing Medan City's Original Regional Income (PAD): A Case Study Of The Medan City Regional Revenue Agency (BAPENDA) - Sari Simatupang; Mifha Rizkina; Tengku Eka Susilawaty (Journal of Management, Economic, and Accounting, 2026)
This study aims to analyze the potential of Entertainment Tax and Restaurant Tax in increasing the Local Own-Source Revenue (PAD) of Medan City. The background of this research is the suboptimal realization of PAD from the entertainment and restaurant sectors, even though Medan City has experienced rapid growth in the culinary and entertainment industries. The research method used is descriptive quantitative with a macro approach, namely the calculation of tax potential based on sectoral Gross Regional Domestic Product (GRDP) data of Medan City for the 2020–2024 period. Data were obtained from the Medan City Revenue Agency (Bapenda) and official publications of the Central Statistics Agency (BPS). The results show that the potential of entertainment tax and restaurant tax fluctuates from year to year. In general, although the calculated potential shows an increasing trend, the actual realization has not yet reached its optimal capacity due to low taxpayer compliance, lack of supervision, and the limited implementation of local tax digitalization. The contribution of entertainment tax and restaurant tax to Medan City’s PAD is still in the moderate category. Therefore, more effective intensification and extensification strategies are needed. Optimizing these two types of taxes is expected to strengthen the region’s fiscal independence and enhance the capability of the Medan City Government in financing development.